Development of a nutraceutical bioproduct with mineral, protein and antiparasitic supplements for dairy goats exploited in northeastern Brazil (Research, Society and Development, 2023)
This work aimed to test mineralizing blocks for supplementation of goats in the region of Pentecoste, Ceará. Solid blocks made up of protein fractions, macro and micro minerals, added with powdered coconut water and active chemical molecules were used to control endoparasitosis and ectoparasitoses. In the period of 60 (sixty) days of ad libitum availability of the blocks for the animals, they were weighed and controlled for the analysis of the elimination of blood parasites, and serological tests for the diagnosis of helminthiasis present during the duration of supplementation. After 60 days of treatments, the animals showed better weight gain, a lower rate of eggs per gram of feces, and a lower incidence of eimerosis. The mineral and protein supplementation gave the animals a better productive and sanitary performance, demonstrating that the use and adoption by goat producers of this technological innovation, will allow the animals a nutritional source focused on the reality of the goat farm with a cost/cost ratio. favorable benefit.